Behind the Peritoneum and Back of the Mind: Consideration of Retroperitoneal Sarcomas as a Differential Diagnosis - Ruo Wen Wong; Shu Jenn Moh; Rosdara Masayuni Mohd Sani; Siti Fareeda Ahmad Nor Anuar (USIM Press, 2024)
Vol. 8 (2022): Special Issue on Communicable and Non-Communicable Disease, Multidisciplinary Case Reports